Stampidine as a Novel Nucleoside Reverse Transcriptase Inhibitor with Potent Anti-HIV Activity - Uckun, Fatih M. (Arzneimittelforschung, 2006)
Stavudine (STV, d4T, 2',3'-didehydro-3'-deoxythymidine, CAS 3056-17-5) is a standard anti-HIV drug. Stampidine (STAMP, DDE-113, HI-113, N-[p-(4-bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester, CAS 217178-62-6) is a novel aryl phosphate derivative of stavudine with more potent anti-HIV activity and more favorable pharmacodynamic features. The remarkable potency of stampidine against clinical HIV-1 isolates with NRTI- or NNRTI-resistance (NRTI, nucleoside reverse transcriptase inhibitor; NNRTI, non-nucleoside reverse transcriptase inhibitor) warrants the further development of this new anti-HIV agent.
Keywords: Anti-HIV agents; Antiretroviral therapy; N-[p-(4-Bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester; CAS 3056-17-5; CAS 217178-62-6; DDE-113; HI-113; Stampidine, clinical trials, pharmacology; Stavudine